Sunday

April 20, 2014

April 20, 2014

Posted by **paulina** on Sunday, September 5, 2010 at 10:56pm.

How do I use the quadratic formula to solve this because I am totally new at this and need help? Please show me the steps for this equation,so I will be able to do it own my own. Thank you.

- algebra -
**Quidditch**, Sunday, September 5, 2010 at 11:34pm1. Make sure the equation is in the form:

ax^2 + bx + c = 0, which your problem is.

2. Use the quadratic formula:

x1 = (-b + (b^2 - 4ac)^(1/2))/(2a)

x2 = (-b - (b^2 - 4ac)^(1/2))/(2a)

You can check your answers by substituting into the original equation.

**Related Questions**

Math - Use the quadratic formula to solve each of the following quadratic ...

Algebra - Find two consecutive positive integers such that the sum of the square...

Algebra 2 help!!! - What value completes the square for the expression? x2 + 14x...

math - (4.35E-2 - x)(7.56E-2 -x ) ============================ (0.324 + 2x)2 ...

algebra - use the quadratic formula to solve the equation 2x^2-3x=-6

math - how many times does the graph of y= 2x squared -2x+3 intersect the x-axis...

pre-cal - What are the steps for solving this? Directions Use the quadratic ...

Algebra - I need help with using the quadratic formula to solve this equation: 2...

algebra - solve the polynomial y=2x^2-4x+1 For Further Reading algebra - Reiny, ...

Algebra 1 - Use the quadratic formula to find the x value that will solve the ...